ERROR CORRECTION TECHNIQUES IN LANGUAGE TEACHING (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2025)
Error correction plays a crucial role in language teaching, helping learners to identify and overcome their mistakes while developing accurate language skills. Various techniques can be applied, such as explicit correction, recasts, elicitation, peer correction, and self-correction. Effective error correction fosters learners’ confidence, enhances communication skills, and promotes long-term language retention. Teachers need to select appropriate methods depending on learners’ age, proficiency level, and learning context.